2016
DOI: 10.30955/gnj.001775
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis and mapping of aridity over Greek areas with different climate conditions

Abstract: Assessment of aridity conditions prevailing in a certain area is essential for the research on climate and climate change. Greece is characterized by a variety of climatic conditions such as drought conditions or flooding phenomena. The current study focuses on three selected areas within Greece that present different climatic characteristics due to their location and aims to analyze and compare the aridity conditions prevailing in these areas. Aridity conditions were estimated using the Aridity Index (AI). Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…1 and 5). The greater aridity in the Eastern part of the Peloponnese compared with the mountains of Turkey (Türkeş 2003;Ünal et al 2003;Panagiotis et al 2013;Paparrizos et al 2016) did not seem to influence the species' geographic range; however, it did affect absolute numbers, with just single dead individuals of J. drupacea observed on the shallow soil (Maerki, personal communication).…”
Section: Climatic Determinants Of Geographic Rangementioning
confidence: 99%
“…1 and 5). The greater aridity in the Eastern part of the Peloponnese compared with the mountains of Turkey (Türkeş 2003;Ünal et al 2003;Panagiotis et al 2013;Paparrizos et al 2016) did not seem to influence the species' geographic range; however, it did affect absolute numbers, with just single dead individuals of J. drupacea observed on the shallow soil (Maerki, personal communication).…”
Section: Climatic Determinants Of Geographic Rangementioning
confidence: 99%
“…The reduction in the potential niche of J. turbinata is more apparent in the pessimistic scenario RCP8.5, in which the temperature would increase by approximately 2°C, precipitation would decrease and there would be a general increase in climate aridity (Allen et al, 2010;Born et al, 2008;Díez-Garretas et al, 2019;Giannakopoulos et al, 2009;Giorgi & Lionello, 2008;Panagiotis et al, 2013;Paparrizos et al, 2016;Türkeş 2003).…”
Section: Past and Future Geographic Rangementioning
confidence: 99%
“…In our study, precipitation was found to determine the potential niche ranges of the J. phoenicea complex to a very high degree. The predicted reduction in precipitation during spring and summer will increase aridity (Giannakopoulos et al, 2009;Panagiotis et al, 2013;Paparrizos et al, 2016) and will also raise tree mortality (Walas et al, 2019). Drought during the summer period has previously provoked an increase in the rate of direct die-out of juniper specimens in several regions around the Mediterranean Sea (Berger & Heurteaux, 1985;Elmahdy & Mohamed, 2016;Lloret & Granzow-de la Cerda, 2013; personal observations).…”
Section: Th R E At Smentioning
confidence: 99%